2016
DOI: 10.1016/j.pediatrneurol.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Lessons of Tuberous Sclerosis: The 2015 Hower Award Lecture

Abstract: Tuberous sclerosis complex is a dominantly inherited disorder that variably affects the brain, skin, kidneys, heart, and other organs. Its neurological manifestations include epilepsy, autism, cognitive and behavioral dysfunction, and giant cell tumors. A mutation of either TSC1 or TSC2 can cause tuberous sclerosis complex. Their two gene products, hamartin and tuberin, form a physical complex which normally inhibits protein synthesis mediated through the mechanistic target of rapamycin, so a TSC1 or TSC2 muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 95 publications
1
26
0
5
Order By: Relevance
“…Of interest, a phase 3 clinical trial showed efficacy in reducing seizure frequency in refractory epilepsy associated with TSC (French et al ., ). Clinical trials are currently ongoing with mTOR inhibitors in patients suffering TSC, ASD and PTEN‐related disorders (Roach, ; http://www.ClinicalTrials.org).…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…Of interest, a phase 3 clinical trial showed efficacy in reducing seizure frequency in refractory epilepsy associated with TSC (French et al ., ). Clinical trials are currently ongoing with mTOR inhibitors in patients suffering TSC, ASD and PTEN‐related disorders (Roach, ; http://www.ClinicalTrials.org).…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…The most common cardiac finding of TSC is rhabdomyoma, which may be detected by ultrasonography in at least 50% of newborns between 20 and 30 weeks of gestation. Patients may be asymptomatic but may also present with severe heart failure or, owing to a compression of the cardiac conduction system, arrhythmia [1,2,18] . Rhabdomyomas in our patients did not produce any symptoms, and echocardiographic examination revealed no form of arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, in 1880, Bourneville described the condition more in depth. Since then, the term TSC was used to describe the condition [1] . Mental retardation, convulsions, and adenoma sebaceum form the diagnostic triad of the condition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tubers growing in the brain are the main factors contributing to high morbidity and mortality in TSC. Brain involvement is often associated with the presence of epilepsy and TAND (Tuberous sclerosis Associated Neuropsychiatric Disorders) 3 . Clinical diagnosis of TSC is based upon identification of agreed and published major and minor diagnostic criteria 4,5 .…”
Section: Introductionmentioning
confidence: 99%